MOBILE MECHANICAL DEVICE FOR VINEYARD CARE AND PRELIMINARY SYNTHESIS OF ITS MAIN PARAMETERS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
In order to facilitate the process of caring for vineyards, to save the physical strength of gardeners, the authors offer gardeners a new "Mobile mechanical ladder" - a mobile device.